Wave climate variability along the coast of Brazil over te past century - Cotrim, Camila de Sá (2021)
Changes in the atmosphere and ocean patterns and the intensification of extreme events in the past decades are often suggested as consequences of Climate Change. Understanding the wave climate and its long-term variability is crucial for environmental science and engineering applications. Wave climate studies in the South Atlantic Ocean are limited and there is a lack of observational data. This study aims to describe the evolution of the wave climate along the coast of Brazil in the last century, by performing statistical analysis of critical wave parameters (significant wave height – Hs; peak period – Tp; mean wave direction – Dir). The tool used was the first reanalysis of the 20th century (1900-2010, ERA-20C) developed by the European Centre for Medium-Range Weather Forecasts (ECMWF). Regarding the evolution of the wave parameters, three behavioral groups were established: southern, central and northern regions. Overall, a strong seasonality of waves was observed with the most energetic waves occurred during the Austral winter, with exception of the north region, which showed its most energetic waves during the Austral summer. The analysis of the main South Atlantic climate indices showed that the key ones influencing the wave climate in the southern and central sectors are the Atlantic Multidecadal Oscillation (AMO) and the Tropical South Atlantic Index (TSA) and in the northern region, the Atlantic Meridional Mode (AMM). The most relevant features of the wave climate temporal variability included, peaks of Hs and Tp in the 1910s and 1940s and a positive trend of significant wave height increase starting in the 1970s, with higher increasing rates for extreme waves than for mean conditions. This study concludes that the most likely reasoning behind this rising trend of Hs are the association to the Southern Annular Mode (SAM) and the AMM, the increased hurricane activity, and the upper oceanic warming.